Prototipe Robot Pemantau Suhu Dalam Zona Kebakaran Gedung Menggunakan Telemetri Jaringan Nirkabel - Indra Gunawan; Imam Fathurrahman (Infotek: Jurnal Informatika dan Teknologi, 2018)
The building fire can be a serious problem that could Interfere economic stability. Firefighters often have problems in handling if they are in the building there is fog or smoke. Therefore, the presence of this monitoring system is expected to present the data in the form of temperature information in the fire zone to help them. This study starts from the collection of materials and equipment, hardware design stage in the form of a wheeled robot while the design of the software comprising a transmitter section is a microcontroller program and the interface program as a receiver. The research result mobile robot can move properly with the remote control within a distance of 20 m. Video on this robot can be displayed in realtime within a distance +15 m of the screen Because the raspberry pi 3 has a coverage area that is not so far away as well as a temperature sensor capable of measuring a very good accuracy in the range of 250C-500CDOI : 10.29408/jit.v1i2.904